Experimental and modeling studies on continuous liquid removal in horizontal gas wells - Lin, Jingde; Xu, Siyuan; Liu, Yinhua (Frontiers in Earth Science, 2023)
The potential risks of liquid-loading can be significantly decreased by precisely calculating the minimum gas flowrate required for continuous liquid removal in gas wells and using suitable deliquification technology beforehand. Due to lack of comparative studies with liquid-loading characteristics, existing prediction models are not very adaptable in the course of the application. So as to investigate the flowing behavior of liquid film under different conditions, visual experiment was conducted. The findings indicate that as the inclined angle increases, the liquid-film-reversal gas velocity increases initially before decreasing. The maximum velocity of liquid-film-reversal is around 55°. The liquid-film-reversing gas velocity increases linearly along with the rise in superficial liquid velocities. The liquid-film-reversal gas velocity likewise increases linearly as the superficial liquid velocities. The analysis findings also indicate that several dynamic liquid-loading symptoms of the gas well are inconsistent with the liquid-film-reversal criterion, meaning that the gas well does not instantly follow the liquid-film-reversal. On the basis of our experimental findings, a new liquid-loading commencement criteria was then developed. As a result, this research suggests a novel model for evaluating liquid-loading in gas wells. The model's accuracy was found to be as high as 85.7% by looking at 14 gas wells and perform better than other models in the Coleman dataset, which can theoretically enable the prediction of liquid-loading in gas wells.